Breast Cancer Survivorship Programme: Follow-Up, Rehabilitation, Psychosocial Oncology Care. 1st Central-Eastern European Professional Consensus Statement on Breast Cancer - Zsuzsanna Kahán; István Szántó; Rita Dudás; Zsuzsanna Kapitány; Mária Molnár; Zsuzsa Koncz; Mónika Mailáth (Pathology and Oncology Research, 2022)
Follow-up includes ongoing contact with and health education of the patient, surveillance and control of the adverse effects of surgery, oncological therapies or radiotherapy, screening of metachronous cancers, and comprehensive (physical, psychological and social) patient rehabilitation, which may be enhanced by a healthy lifestyle. Primary attention should be paid to early detection and, when needed, curative treatment of local/regional tumour recurrences. Similarly, with the hope of curative solution, it is important to recognize the entity of a low-mass and relatively indolent recurrence or metastasis (oligometastasis); however, there is still no need to investigate distant metastases by routine diagnostic imaging or assess tumour markers. Below there is a list of possible sources of support, with respect to adjuvant hormone therapy continued during long-term care, social support resources, pivotal points and professional opportunities for physical and mental rehabilitation. Individual solutions for specific issues (breast cancer risk/genetic mutation, pregnancy) are provided by constantly widening options. Ideally, a complex breast cancer survivorship programme is practised by a specially trained expert supported by a cooperative team of oncologists, surgeons, breast radiologists, social workers, physiotherapists, psycho-oncologists and psychiatrists. The approach of follow-up should be comprehensive and holistic.